Transfer of Inuit qaujimajatuqangit in modern Inuit society - Laugrand, Frédéric; Oosten, Jarich (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2009)
This paper explores the nature and transfer of Inuit knowledge. Using our experiences in setting up workshops with elders and youths in the past 10 years, we argue that the notion that Inuit qaujimajatuqangit can be viewed as a corpus of knowledge that can be integrated into academic programs is necessarily flawed. We suggest that more room should be given to Inuit elders and their knowledge by adapting the school system to Inuit perspectives rather than the reverse.